ANALISIS HARGA ,KUALITAS PRODUK,PROMOSI TERHADAP KEPUASAAN KONSUMEN MEMBELI MAMYPOKO PANTS DI KABUPATEN TULUNGAGUNG - Oktaviana, Yastika; Zulistiani; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to analyze the effect of price, product quality, promotion on consumer satisfaction in buying Mamypoko pants in Tulungagung district. By taking people who bought Mamypoko Pants in Tulungagaung Regency, using the incidental sampling method, the main data from the sample was collected using a questionnaire instrument that included Price, Product Quality, Promotion of Consumer Continuity to Buy Mamypoko Pants in Tulungagung Regency. The data analysis technique used the Classical Assumption Test. , Multiple linear test , Coefficient of determination , F test . The result of the research is that price has an influence on consumer satisfaction buying Mamypoko Pants in Tulungagung Regency , Product quality has an influence on consumer satisfaction buying Mamypoko Pants in Kabu Tulungagung patent, Promotion has an influence on consumer satisfaction buying Mamypoko Pants in Tulungagung Regency. Price, Product Quality, Promotion variables affect consumer satisfaction.